The Role of Islamic Educational Institutions in The Reconstruction of Social Values of Society - Susanti; Khozin (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Study This background behind the importance of role institution Islamic education, in particular cottage modern Islamic boarding schools in forming and reconstructing values social society in the middle dynamics change increasingly social complex. Existence Cottage Al-Hikmah Modern Islamic Boarding School, sub-district Utan Sumbawa Regency becomes significant for reviewed, because no only functioning as institution education, but also as agent transformation social contribution to coaching character and values social public around. Research This aim for analyze values social development in the educational process Islamic boarding school as well as the impact to reconstruction mark social community. The method used in study This is approach qualitative with technique data collection through observation, interviews, and documentation. Selection informant done with purposive sampling technique, namely choose the subject under consideration own information relevant to focus research. Then, the data analyzed in a way descriptive for identify pattern mark social development as well as the impact in life community. Research results show that Cottage Al-Hikmah Modern Islamic Boarding School, sub-district Utan Sumbawa district develops values social like religiosity, discipline, independence, and responsibility answer social through system education integrated and life collective santri. Values the impact on society around in form strengthening norm religious, improvement concern social, as well as change pattern behavior going to a better life regular and productive. Therefore that, can concluded that Islamic boarding school own role strategic in reconstruct mark social society and become agent change relevant social in modern context.